2021
DOI: 10.3390/s21206741
|View full text |Cite
|
Sign up to set email alerts
|

In-Network Data Aggregation for Ad Hoc Clustered Cognitive Radio Wireless Sensor Network

Abstract: In cognitive radio wireless sensor networks (CRSN), the nodes act as secondary users. Therefore, they can access a channel whenever its primary user (PU) is absent. Thus, the nodes are assumed to be equipped with a spectrum sensing (SS) module to monitor the PU activity. In this manuscript, we focus on a clustered CRSN, where the cluster head (CH) performs SS, gathers the data, and sends it toward a central base station by adopting an ad hoc topology with in-network data aggregation (IDA) capability. In such n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This SS module plays a crucial role in ensuring that the secondary nodes opportunistically access the spectrum without causing interference to the PU [6]. Cognitive radio (CR) networks achieve high spectral efficiency by facilitating the sharing of frequency bands between two types of users: the PU and the SU.…”
Section: Adopting Cognitive Methods In Wsnmentioning
confidence: 99%
“…This SS module plays a crucial role in ensuring that the secondary nodes opportunistically access the spectrum without causing interference to the PU [6]. Cognitive radio (CR) networks achieve high spectral efficiency by facilitating the sharing of frequency bands between two types of users: the PU and the SU.…”
Section: Adopting Cognitive Methods In Wsnmentioning
confidence: 99%
“…Mortada et al [9] discussed the working of CRSN where sensor nodes act as secondary users and can access the channel when the primary user is not present. However, this process is opportunistic and is performed without PUs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mortada et al consider the cognitive radio wireless sensor networks (CRSN) and how to cluster a CRSN, such that the cluster head (CH) performs Spectrum Sensing (SS), gathers the data, and sends it toward a central base station by adopting an ad hoc topology with an in-network data aggregation (IDA) capability [ 1 ]. The authors showed that the energy consumed by the data transmission decreases, while the total consumed energy of SS increases, since more CHs need to perform SS before transmitting.…”
Section: Overview On Contributionsmentioning
confidence: 99%